ANALISIS POTENSI, EFEKTIFITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SLEMAN - Rofian Pujiasih; Dewi Kusuma Wardani (Jurnal Akuntansi, 2014)
This study aims to determine the potency, effectiveness and contribution tax in Sleman district. To calculate the potential and effectiveness of hotel tax used several variables: number of to define average, the number of days in a year, and hotel tax rates. As for the contribution of data use hotel tax revenues and actual revenues revenue. This study used descriftif research and the method of documentation that is by collecting data that is used to collect secondary data from reports of hotel tax revenue, the rules relating to tax hotel also see and obtain reference books on hotel tax, reports the results of previous studies and scientific papers .These results indicate that the potential for very large hotel tax receipts well above realization Taxes, effectiveness and contribution no hotel taxes low. The results of this study also shows that the potential is not being realized Taxes optimally and there are some things that need to be re- correction and should be addressed by the government of Sleman Regency . Keywords : Potential, Effectiveness, Contributions, hotel taxes and local revenue ( PAD ) .